2016
DOI: 10.1080/00222895.2016.1204266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcranial Direct Current Stimulation Combined With Virtual Reality Training on Balance in Children With Cerebral Palsy: A Randomized, Controlled, Double-Blind, Clinical Trial

Abstract: The authors' aim was to investigate the effects of continuous transcranial direct current stimulation (tDCS) combined with virtual reality training on static and functional balance in children with cerebral palsy (CP). Twenty children with CP (6 girls and 14 boys; M age = 7 years 6 months ± 2 years) were randomly allocated to two groups. The experimental group received active tDCS and the control group received sham stimulation during the 10 sessions of virtual reality mobility training protocols. The children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 22 publications
1
37
0
10
Order By: Relevance
“…29 30 Moreover, a non-invasive brain stimulation method (tDCS) will be employed to facilitate motor cortical excitability in the areas subjacent to stimulation to enhance the effects of motor control and learning. [37][38][39][40][41][42] Lazzari et al 37 demonstrated the efficacy of the combination of tDCS and VR in potentiating motor effects on balance and functional mobility in children with cerebral palsy. 37 This document offers a detailed description of a randomised, controlled, double-blind, clinical trial designed to determine the effectiveness of VR training combined with tDCS on upper limb movements in individuals with DS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 30 Moreover, a non-invasive brain stimulation method (tDCS) will be employed to facilitate motor cortical excitability in the areas subjacent to stimulation to enhance the effects of motor control and learning. [37][38][39][40][41][42] Lazzari et al 37 demonstrated the efficacy of the combination of tDCS and VR in potentiating motor effects on balance and functional mobility in children with cerebral palsy. 37 This document offers a detailed description of a randomised, controlled, double-blind, clinical trial designed to determine the effectiveness of VR training combined with tDCS on upper limb movements in individuals with DS.…”
Section: Discussionmentioning
confidence: 99%
“…The results of clinical trials have demonstrated its considerable potential in the treatment of neurological disorders and the investigation of processes of cortical excitability modulation. [37][38][39][40][41][42] Moreover, this type of intervention offers a better condition for sham stimulation, which confers greater specificity to the findings. 39 40 In the rehabilitation process, the aim of neuromodulating techniques is to enhance local synaptic efficiency and alter the maladaptive plasticity pattern that emerges after a cortical injury.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have produced positive results when combining VR and tDCS therapies in stimulating the lower limbs for gait improvement ( 12 ) and balance ( 28 , 29 ). However, no studies have investigated VR and tDCS interventions using an upper limb motor task, which might benefit different clinical conditions of individuals with CP.…”
Section: Introductionmentioning
confidence: 99%
“…This game was chosen based on its potential to stimulate motor coordination and improve physical fitness. The participant will simulate walking or running by lifting the knees in a stationary march, resulting in constant displacement of the center of gravity, involving symmetry, alternating actions and rhythm, which are essential to gait (26) .…”
Section: Virtual Reality Gait Trainingmentioning
confidence: 99%